Avaliação das condições microbiológicas da água e de peixes do Rio Mearim, no município de Bacabal-MA - Paiva, Thaís Vieira (2016)
Contaminated waters not only directly affect human health but also cause serious damage to the aquatic biota, causing deterioration in fish quality. The objective was to evaluate the hygienic-sanitary conditions of the water and the fresh fish from the Mearim river in BacabalMa during the rainy season, through the identification of the potentially pathogenic bacteria. A total of 54 samples of water and 54 samples of fresh fish that were colected between October 2015 and March 2016, which were submitted to the quantification of total and thermo tolerant coliformes by the thechnique of Most Probable Number (MPN/g) and Clostridium sulphite reducing research. After that, the biochemical identification of isolated bacteria coming from the Enterobacteriaceae family was performed using commercial biochemical tests. The results showed that the microbiological quality of the water and the fish is unsatisfactory due to the high contamination rates of thermotolerant coliforms, being below the microbiological quality standards, as well as the the presence of total coliforms and Clostridium sulphite reducers in considerable concentrations both in water and in fish. The water’s contamination by coliforms was significantly higher than in the fishes, in the dry season as well as in the rainy season. Escherichia coli was the bacterium with the highest frequency of isolation in water samples, both in the dry season and in the rainy season. Citrobacter diversus and Serratia odorífera also had important isolation frequency in the water samples of the two seasons. In the fish samples, the highest frequency of identification was also from Escherichia coli. Serratia odorífera and Citrobacter diversus also had relevant frequencies in the dry season. In the rainy season Escherichia coli kept the highest frequency of isolation, followed by Serratia odorífera and Citrobacter freundii.